Link and Match Penelitian dan Pengembangan Pelayanan Kesejahteraan Sosial - Mumu Suherlan (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2013)
The Ministry of Social Affairs as the main actor on social welfare services should provide appropriate social policies to overcome the current social problems. Research and development is a bridge to reach social welfare services effectiveness and efficiency. The linkage of research and development products and their applications by operational programs of social services should be established as good as possible in order to build proportional qualified interactive suitability, itâ€™s called as link and match between research and development products with the absorbance ability of operational unit. B2P3KS as a researchÂ and development organization of social welfare services models maker should refers problems and strategic issues to policy level that faced by operational units. Moreover, research and development also should referes problems and strategic issues to empirical level. Through link and match concept, research and development products are expected to able to solve and overcome social problems and increase social welfare.